Towards a capability maturity model for a cyber range - Aschmann, Michael Joseph (Rhodes University, Faculty of Science, Department of Computer Science, 2020)
This work describes research undertaken towards the development of a Capability Maturity Model (CMM) for Cyber Ranges (CRs) focused on cyber security. Global cyber security needs are on the rise, and the need for attribution within the cyber domain is of particular concern. This has prompted major efforts to enhance cyber capabilities within organisations to increase their total cyber resilience posture. These efforts include, but are not limited to, the testing of computational devices, networks, and applications, and cyber skills training focused on prevention, detection and cyber attack response. A cyber range allows for the testing of the computational environment. By developing cyber events within a confined virtual or sand-boxed cyber environment, a cyber range can prepare the next generation of cyber security specialists to handle a variety of potential cyber attacks. Cyber ranges have different purposes, each designed to fulfil a different computational testing and cyber training goal; consequently, cyber ranges can vary greatly in the level of variety, capability, maturity and complexity. As cyber ranges proliferate and become more and more valued as tools for cyber security, a method to classify or rate them becomes essential. Yet while a universal criteria for measuring cyber ranges in terms of their capability maturity levels becomes more critical, there are currently very limited resources for researchers aiming to perform this kind of work. For this reason, this work proposes and describes a CMM, designed to give organisations the ability to benchmark the capability maturity of a given cyber range. This research adopted a synthesised approach to the development of a CMM, grounded in prior research and focused on the production of a conceptual model that provides a useful level of abstraction. In order to achieve this goal, the core capability elements of a cyber range are defined with their relative importance, allowing for the development of a proposed classification cyber range levels. An analysis of data gathered during the course of an expert review, together with other research, further supported the development of the conceptual model. In the context of cyber range capability, classification will include the ability of the cyber range to perform its functions optimally with different core capability elements, focusing on the Measurement of Capability (MoC) with its elements, namely effect, performance and threat ability. Cyber range maturity can evolve over time and can be defined through the Measurement of Maturity (MoM) with its elements, namely people, processes, technology. The combination of these measurements utilising the CMM for a CR determines the capability maturity level of a CR. The primary outcome of this research is the proposed level-based CMM framework for a cyber range, developed using adopted and synthesised CMMs, the analysis of an expert review, and the mapping of the results.
Keywords: Computer software -- Development; Computer security